ANALISIS KERUSAKAN BOLT TANDEM MAIN PUMP PADA UNIT EXCAVATOR HITACHI EX 2500 (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2020)
The pump is the main component of the hydraulic system that functions to drain oil to all components that work in the unit. The damage to the main pump is the broken bolt tandem main pump makes the main pump external leak. As a result of the broken bolt tandem on the main pump in half of the life time pump makes losses and causes dissatisfaction for the customers.Testing the vibration of the tie bolt tandem pump using a KPM test bench in each tie bolt tandem plays the pump with a vibrator sensor installed, to determine the amount of vibration received during the operating unit. The condition of resonance confirmation on KPM test bench obtained by the results of vibration displacement of 35 µ, and it is known that above the standard value of 25 µ, that is the amount of vibration received by the tie bolt tandem pump during the operation unit and causes the tandem tie bolt to break.